Advances of nanomaterial applications in oral and maxillofacial tissue regeneration and disease treatment. (8th October 2020) - Ding, Qinfeng; Cui, Jinjie; Shen, Hangqi; He, Chuanglong; Wang, Xudong; Shen, Steve G. F.; Lin, Kaili
Abstract: Using bioactive nanomaterials in clinical treatment has been widely aroused. Nanomaterials provide substantial improvements in the prevention and treatment of oral and maxillofacial diseases. This review aims to discuss new progresses in nanomaterials applied to oral and maxillofacial tissue regeneration and disease treatment, focusing on the use of nanomaterials in improving the quality of oral and maxillofacial healthcare, and discuss the perspectives of research in this arena. Details are provided on the tissue regeneration, wound healing, angiogenesis, remineralization, antitumor, and antibacterial regulation properties of nanomaterials including polymers, micelles, dendrimers, liposomes, nanocapsules, nanoparticles and nanostructured scaffolds, etc. Clinical applications of nanomaterials as nanocomposites, dental implants, mouthwashes, biomimetic dental materials, and factors that may interact with nanomaterials behaviors and bioactivities in oral cavity are addressed as well. In the last section, the clinical safety concerns of their usage as dental materials are updated, and the key knowledge gaps for future research with some recommendation are discussed. This article is categorized under: Implantable Materials and Surgical Technologies > Nanomaterials and Implants Implantable Materials and Surgical Technologies > Nanotechnology in Tissue Repair and Replacement Abstract : Current advances, limitations and future prospects for nanomaterial applications in oral and craniofacial tissue regeneration and disease treatment.